A new species of Pseudopaludicola Miranda-Ribeiro (Anura: Leptodactylidae: Leiuperinae) from eastern Brazil, with novel data on the advertisement call of Pseudopaludicola falcipes (Hensel) - de Andrade, Felipe Silva; Haga, Isabelle Aquemi; Lyra, Mariana Lúcio [UNESP]; Leite, Felipe Sá Fortes; Kwet, Axel; Haddad, Célio Fernando Baptista [UNESP]; Toledo, Luís Felipe; Giaretta, Ariovaldo Antonio (Magnolia Press, 2018)
The Neotropical genus Pseudopaludicola includes 21 species, which occur throughout South America. Recent studies suggested that the population of Andaraí, in the state of Bahia, is an undescribed species, related to P. pocoto. Herein we formally describe this new species from lowlands of eastern Brazil. Recognition of this new species is supported by adult morphology, advertisement call, karyotype, and molecular data. It is diagnosed mainly by its small size, terminal phalanges knobbed (lack any expansion of the digital tips), proportionally short hindlimbs, 11 pairs of chromosomes, and advertisement call composed of series of three-pulsed notes, emitted at a high rate. In addition, we report for the first time the presence of P. pocoto in the campo rupestre (rupestrian grasslands) of Chapada Diamantina, a population with a much darker dorsal coloration than the population from the type locality. We also redescribed the advertisement call of P. falcipes based on recordings from topotypic males.
Keywords: Advertisement call; Bioacoustics; Integrative taxonomy; Morphologically cryptic species; Pseudopaludicola pocoto